Simulation of a manufacturing system for low volume high mix manufacturing (A) - Hu, Juntian (2019)
This paper aims to build simulation of a manufacturing system for low volume high mix manufacturing. By managing similarities between different tasks using a simulation, productivity of a low volume high mix manufacturing system can be improved. This project is to build a Festo line manufacturing simulation system, which has been already set practically in delta lab. Discrete event simulation is used to manage event-driven systems which transits state depend on event occurred rather than time. When an event occurs, the state in the system will change, and no state is between consecutive events. In this project, discrete event simulation is used to build an event-driven system. The robot movement, sensor info and machine operation will be realized in this 3D simulation software Visual Components as well. PLC program is to connect to Visual Components in order to represent the program in a 3D method.